MONITORING ASSESSMENT OF THE SURFACE WATER QUALITY WITHIN THE AREAS FOR THE MUNICIPAL SOLID WASTE DISPOSAL - Azimov, O.; Kuraeva І.; Trofymchuk, O.; Zlobina, K.; Karmazynenko, S. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The monitoring ecological hydro-geochemical investigations for the surface waters of the north-western part of Landfill No 5 for the municipal solid waste disposal and the adjacent area are carried out. Based on analyses of surface water samples taken from the existing ponds, it was found that they are polluted by wastewater with the high content of predominantly organic toxicants. Most likely the latter comes from both the Sections and ponds-collectors of leachate or from the pig farm, which is located near the Landfill but hypsometrically higher in relief. More studies are required in order to specify the answer. On the other hand, surface waters beyond the Landfill area are characterized by the ecological and hydrogeochemical indicators, which are not higher than the maximum allowable concentrations, although they are higher than the background ones. This indicates that the considerable outflow of chemical pollutants together with the surface waters from the north-western Landfill No 5 area beyond its borders is absent for more than a year. Only the short-time periodic monitoring of the water bodies within the territory of interest would allow to determine such time intervals when water could be polluted by various toxicants.